An Industry 4.0: Strategy Direction Of An Airline Operations Performance - Dewi Nusraningrum; Tri Mayang Mekar; Jajang Gunawijaya (Jurnal Manajemen Indonesia, 2021)
Air transport is an industry 4.0 sector of priority that continues to evolve as the era becomes the backbone of a country's economy. The opening of the economic market in all regions of the world has increased the complexity of air transportation, including in Indonesia. In this decade as the development of technology and the 4.0 industry, the air plane remains the choice of people to explore the world and also the movement of people from one place to another is rapidly secured funds. The strategy to compete with the airline is to improve flight image in Indonesia by improving the performance of aviation operations. This research aims to analyse and evaluate the performance of aviation operations in Indonesia from the company's perspective. The survey method was conducted through the dissemination of questionnaires to respondents with purposive sampling techniques netted 200 aviation employees in Indonesia. The data collected is processed using the Structural Equation Model - Partial Least Square. The results showed; Strategy direction proved to affect process management, process management proved no effect on operation performance, strategy direction has no effect on Operation performance, strategy direction proved to affect human resources management, human resource management proved to be no impact on Operation performance, Process management proved unable to fully mediation the relationship between strategy direction with operating performance, HR management proved not to fully mediation the relationship between strategy direction to operating performance. So it can be said the strategy direction of the company directly affects the flight operation performance. Keywords— Strategy direction; process management; human resource management; operation performance